Correlation between percutaneous patent foramen ovale closure and recurrence of unexplained syncope - Wang, Xianwen; Liu, Xiangwei; Zheng, Lulu; Liu, Yubo; Guan, Zhengyan; Dai, Jingyi; Chen, Xiaobin (Frontiers in Neurology, 2023)
Background: The relationship between patent foramen ovale (PFO) and unexplained syncope is still to be illustrated. The aim of this study was to explore the outcomes as well as the prognostic factors for the recurrence of syncope after PFO closure. Methods: Patients with both large right-to-left shunting (RLS) PFO and unexplained syncope visited the cardiovascular department of Xiangya Hosipital Centre South University from 1st January 2017 to 31st December 2021 were consecutively enrolled to our study. The recurrence rate of syncope was compared between non-closure group (n=20) and closure group (n=91). Results: A total of 111 patients were finally included. After 31.11 ± 14.30 months follow-up, there were only 11% of patients in the closure group had recurrent syncope, which was much lower than that of the non-closure group (11.0% vs. 35%, P=0.018). We further investigated the possibly prognostic factors for syncope recurrence in the closure group and found that: without inducements, preoperational syncope episodes over 5 times, with hypertension, and postoperative 12 months residual RLS are significantly correlated with more recurrence. Conclusions: PFO closure effectively reduced the recurrence of unexplained syncope. The prevention efficacy was prognosticated by factors include, with or without syncope inducements, the frequency of syncope episodes, and whether with hypertension. And the recurrence of syncope was also strongly related with residual shunt post-closure.